Acesso e uso da informação pública: módulo acesso à informação do FALA.BR no contexto do Instituto Federal da Paraíba - Morais, Luciana Silva de (2021)
Nowadays access to information is a pillar of democracy and one of the foundations of fundamental individual and collective Right to exercise of citizenship, guaranteed by the Federal Constitution. It is the heart of all social processes and respect for Human Rights. Since the implementation of Law n. 12.527/2011, Law of Access to Information, obligations have been introduced to elevate transparency level in actions taken by the public sphere and to standardize the communication channels dedicated to Society‘s questions meeting. From this perspective, the creation of the Information to the Citizen Service has established a new reality for the public organs/entities, which has as main challenge to adapt the procedural conducts of information management to attend to the various demands of the society and respect the rights consecrated in the 1988 Constitution. In this sense, the present study has as a general objective to analyze the use of the Fala.BR access to information in Paraiba Federal Institute context module considering the transparency of information. In methodological terms, it corresponds to descriptive research with a qualitative and quantitative approach. Data collection occurred through the indirect observation technique, such as the interview that is composed of two strands of investigative analysis: the real user who seeks the system to obtain access to information and the servers who are responsible for providing the requested information. The final results revealed that the effective users who have an interest in public information produced and/or cost by IFPB are subjects characterized by male gender, who are between 30 and 40 years, graduated, with a profession related to public service and reside, in its majority, in the Northeastern region of Brazil. The obstacles related to institutional poor communication, documentary management, technological resources, lack of professionals with skills for specific areas, and organizational culture are perceived as barriers. It was observed the absence of actions that aim to train servers with an emphasis on the Law of Access to Information. It was identified that, within the context of the environment of the collaborators of the study, the implementation of LAI collaborated to improve in different aspects in the administrative routine. Thus, suggestions are presented that favor the process of meeting social demands, considering the perspective of the practice of passive transparency and active transparency. It is concluded that information is currently a motivating factor that intervenes in the daily life of the human being, resignifying actions and practices and from the perspective of this study of the public sphere, its professionals and users.